Optimization study on preparation of amine functionalized sea mango (cerbera odollam) activated carbon for Carbon Dioxide (CO2) adsorption - Md Ali, Umi Fazara; Azmi, Nur Hidayah; Md Isa, Khairuddin; Aroua, Mohamed Kheireddine; Tan, Ru Shien; Khamidun, Mohd Hairul (Taylor & Francis, 2018)
Activated carbon derived from sea mango (cerbera odollam), SMAC, was developed from phosphoric acid (H3PO4) activation. Box-Behnken Design (BBD) was employed to optimize the surface area of the SMAC. The tested factors were acid concentration (40 to 60%), carbonization temperature (400 to 600°C) and activation time (1 to 3 h). The optimized parameters were 53.75% H3PO4 concentration, 519.8°C of carbonization temperature and 2.3 h of activation time, which resulted in 857.93 m2 /g of BET surface area. The performance of CO2 adsorption was investigated for modified and virgin SMAC. The impregnations of SMACs were done with different amines (AMP, PZ and MEA) to improve its natural adsorption ability and promote nitrogen functional group onto carbon surface with impregnation mass ratio of 2:5 (amine: activated carbon). The effects of adsorption parameters such as activated carbon properties, type of amine used, gas flow rate and adsorbent dosage on breakthrough curves and adsorption bed capacity were evaluated. Reduction in BET surface area indicates that the amine-based chemicals were successfully attached on carbon surface and thus blocked most of the pores on the SMAC particles. The modified surface of SMAC with AMP amine showed the best performance in CO2 adsorption and regeneration with adsorption bed capacity of 23.05 mgCO2/g sorbent. Successful CO2 adsorption via modified surface of SMAC suggested that it is viable to use sea mango as alternative precursor for activated carbon preparation and in application such as CO2 capture.